IS IT A RELATIONAL MARKETING STRATEGY? CLUSTER ANALYSIS @UNIVERSITASMERCUBUANAJAKARTA FACEBOOK POST AND COMMENT - Arissetyanto Nugroho; Tatik Nur Khayati; Yuli Harwani; Janfry Sihite (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract: The objective of the research is to analyze the relational marketing strategy from the application of new media facebook in the private university Facebook account @universitasmercubuanajakarta. 5575 post and comment within the year 2013 collected, 51 irrelevant data excluded from the analysis, and finally there are 1412 post and 4112 comment analyzed. There are 756 accounts generated the post, @universitasmercubuanajakarta post 872 times and there are 84% (633) accounts post 1 time, furthermore there are 97% (735) personal account and 3% (21) organization account. The gender of the 735 personal account are 40% (297) woman and 60% (438) man. There are 2015 account generated the comment, @universitasmercubuanajakarta comments 456 times and there are 90% (1805) accounts comment 1-2 times, furthermore there are 99,99% (2011) personal account and less than 0,01% (4) organization account. The gender of the 2011 personal account are 37% (748) woman and 63% (1267) man. These post and comment interaction confirmed the relational marketing activities @universitasmercubuanajakarta, further cluster analysis conducted and confirmed the application of relational marketing strategy within four main themes which are The Student Achievement, The University External Cooperation, The Employee Class Program & Facilities, and The Information for Prospective & New Students.Keywords: Relational Marketing, @universitasmercubuanajakarta, Facebook Post & Comment, Provalis Research QDA Miner, Cluster Analysis